TIMBER CURTAIN WALL – INNOVATIVE STRUCTURALLY GLAZED UNITISED SYSTEM FOR BUILDING ENVELOPES (Collection of scientific works «Modern structures of metal and wood», 2022)
This  paper  presents  the  results  of  research  conducted  within  R&D  project.  The primary goal was to apply the current state of the art technology in aluminium to a timber-based frames,  but  also  to  improve  the  energy  performance  of  the  building  envelope  and  create environmentally friendly product, which physical, structural and aesthetic performances are equal to or  even  better  than  equivalent  aluminium  systems.  The  developed  TimberCW  is  an  innovative structurally glazed curtain wall system entirely comprised of laminated timber profiles incorporated in a fully prefabricated unitised curtain wall design, where glass panes are bonded by the structural silicone to timber frames. While most current timber curtain wall systems are stick designs, combined with aluminium elements, this new concept introduces timber split mullions and entirely eliminates aluminium structural members, whilst maintaining high weathertightness performance. In order to retain thin cross sections, as they are common for aluminium design, specialised corner connections in timber frame and stainless-steel bracketry has been developed and laboratory tested. Comparative energy  efficiency  analysis  and  condensation  risk  assessment  of  the  TimberCW  vs  fully  unitised aluminium systems of identical overall geometry and structural performance are presented. Full scale laboratory testing has been undertaken and certification obtained, proving the TimberCW concept suitable for project application.